Clinical Outcomes of 5358 Patients Undergoing Direct Open Bypass or Endovascular Treatment for Aortoiliac Occlusive Disease: A Systematic Review and Meta-Analysis. (August 2013) - Indes, Jeffrey E.; Pfaff, Miles J.; Farrokhyar, Forough; Brown, Hillary; Hashim, Peter; Cheung, Kevin; Sosa, Julie Ann
Purpose: To examine clinical outcomes of endovascular and open bypass treatment for aortoiliac occlusive disease (AIOD). Methods: Multiple databases were systematically searched to identify studies on open and endovascular treatment for AIOD published from 1989 to 2010. Studies were independently reviewed for eligibility criteria. Study selection and assessment of methodological quality were performed by two independent reviewers. Assuming between-study heterogeneity due to biases inherent to observational studies, a random effects model (DerSimonian-Laird method) was used for calculation of weighted proportions. Pooled weighted proportions or weighted means are reported. Twenty-nine open bypass studies (3733 patients) and 28 endovascular treatment studies (1625 patients) were analyzed. Results: Weighted mean patient age was 60.4 years for open bypass and 60.8 years for endovascular treatment. Poor preoperative runoff was greater in the open bypass group (50.0% vs. 24.6%, p<0.001). Mean length of hospital stay (LOS) was 13 days for open bypass vs. 4 days for endovascular treatment procedures (p<0.001). The open bypass group experienced more complications (18.0% vs. 13.4%, p<0.001) and greater 30-day mortality (2.6% vs. 0.7%, p<0.001). At 1, 3, and 5 years, pooled primary patency rates were greater in the open bypass group vs. the endovascular cohort (94.8% vs. 86.0%, 86.0% vs. 80.0%, 82.7% vs. 71.4%, respectively; all p<0.001); the same was true for secondary patency [95.7% vs. 90.0% (p=0.002), 91.5 vs. 86.5% (p<0.001), and 91.0% vs. 82.5% (p<0.001), respectively]. Conclusion: Although this study was limited by a paucity of randomized control trials, these results demonstrate superior durability for open bypass, although with longer LOS and increased risk for complications and mortality, when compared to the endovascular approach.